Landmarks and techniques to perform minimally invasive liver surgery: A systematic review with a focus on hepatic outflow. (19th February 2021) - Monden, Kazuteru; Alconchel, Felipe; Berardi, Giammauro; Ciria, Ruben; Akahoshi, Keiichi; Miyasaka, Yoshihiro; Urade, Takeshi; García Vázquez, Alain; Hasegawa, Kiyoshi; Honda, Goro; Kaneko, Hironori; Hoon Kim, Ji; et al.
Abstract: Purpose: In this systematic review, we aimed to clarify the useful anatomic structures and assess available surgical techniques and strategies required to safely perform minimally invasive anatomic liver resection (MIALR), with a particular focus on the hepatic veins (HVs). Methods: A systematic review was conducted using MEDLINE/PubMed for English articles and Ichushi databases for Japanese articles through September 2020. The quality assessment of the articles was performed in accordance with the Scottish Intercollegiate Guidelines Network (SIGN). Results: A total of 3372 studies were obtained, and 59 were selected and reviewed. Due to the limited number of published comparative studies and case series, the degree of evidence from our review was low. Thirty‐two articles examined the anatomic landmarks and crucial structures for approaching HVs. Regarding the direction of HV exposure, 32 articles focused on the techniques and advantages of exposing HVs from either the root or the periphery. Ten articles focused on the techniques to perform a segmentectomy 8 in particularly difficult cases of MIALR. In seven articles, bleeding control from HVs was also discussed. Conclusions: This review may help experts reach a consensus regarding the best approach to the management of hepatic veins during MIALR. Abstract : Highlight This systematic review summarizes and assesses the important anatomy and available surgical techniques for safe performance of minimally invasive anatomic liver resection (MIALR). Of 3372 manuscripts obtained, 59 were selected and reviewed. This review may help experts reach consensus regarding the best approach to manage hepatic veins during MIALR.